SUITABILITY ASSESSMENT OF SOME WELLS WATER FOR IRRIGATION IN WADI ALSHATTI, SOUTH WEST OF LIBYA - Al-Tamimi, Raad A. (Diyala Agricultural Sciences Journal, 2017)
This study was conducted to investigate ionic composition and some chemical properties of some wells water in Wadi Al-Shatti region, South-West of Libya, to assess its suitability for irrigation. The obtained results indicated that most studied samples have been slightly acid to neutral pH with range of 6.5-7.0. Three samples only had slightly alkaline pH with rang of 7.1-7.8. Most samples had high salt content. Electrical conductivity of samples was ranged from 940 to 4890 µS cm-1 . Sodium was the dominant cation. As anion, sulphate dominated in most samples whereas chloride in few. The concentrations of cations in the studied samples were in the order: Na+> Ca2+> K+> Mg2+. Results indicated noticeable low magnesium, and high to very high potassium concentrations. Chloride concentrations were moderately to extremely high. All samples had low concentration of boron, but some have significant amount of nitrate. Most samples had high total hardness which may cause foliar deposits of calcium or magnesium carbonate under overhead irrigation. PHc confirmed that none of the studied samples had a tendency for scaling or corrosion.